What Factors Constitute Structures of Clustering Creative Industries? Incorporating New Institutional Economics and New Economic Sociology into A Conceptual Framework - Ismalina, Poppy (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2012)
Creative industries tend to cluster in specific places and the reasons for this phenomenon can be a multiplicity of elements linked mainly to culture, creativity, innovation and local development. In the international literature, it is pretty well recognized that creativity is frequently characterized by the agglomeration of firms so that creative industries are not homogeneously distributed across the territory but they are concentrated in the space. Three theories are becoming the dominant theoretical perspectives in agglomeration economies theory and they are increasingly being applied in industrial clusters analysis to study the effect of clustering industries. The theories are Marshallâs theoretical principles of localization economies, Schmitzâs collective efficiency and Porterâs five-diamond approach. However, those have adequately theorized neither the institutionalization process through which change takes place nor the socio-economic context of the institutional formations of clustering creative industries. This text begins by reviewing three main theories to more fully articulate institutionalization processes of an economic institution. Specifically, this paper incorporates new institutional economics (NIE) and new economic sociology (NES) to explain the processes associated with creating institutional practices within clustering creative industries. Both streams of institutional theory constitute that economic organizations are socially constructed. Next, this text proposes the framework that depicts the socio-economic context better and more directly addresses the dynamics of enacting, embedding and changing organizational features and processes within clustering creative industries. Some pertinent definitions are offered to be used in a conceptual framework of research about how economic institutions like clustering creative industries constitute their structures.Â Â Â Â